On-line automatic signature verification : a computational intelligence approach - Yue, Andrew Kwok Wai. (2008)
Automatic online signature verification is an intriguing intellectual challenge with many practical applications. Many approaches to automatic signature verification have been proposed in the past several years. After careful investigation of the problem, a new automatic online signature verification system (AOSVS) is proposed in the thesis.